ﻣوﻗف اﻟدوﻟﺔ اﻟﻌرﺑﯾﺔ اﻻﺳﻼﻣﯾﺔ ﻣن اﺣﺗﻛﺎر اﻟﻣواد اﻟﻐذاﺋﯾﺔ اﻟرﺋﯾﺳﺔ ﻓﻲ اﻟﻘرن اﻻول اﻟﮭﺟري (Journal of the College of Education for Women, 2019)
The Prophit had blamed the monopolies, and dispraise the monopoly, dismised it and warned the monopolies that they will face very severe pain. The Prophit had built the right foundation for the trade . He had made the chance of monopoly very few . Inspite of finding some monopolies in his time,he didn’t make price tag. The Rightly guided caliphs didn’t pricing the food-stuff. Umar b. Al-Khatab used many ways to encourage the enterance of the foods- stuff to the markets by the tradesmen of wholesale. The people were sailing directly from them . the tradesmen of wholesale were in competition, so they reduced the prices . but he forbid the monopoly and stopped against it by the scientific ways. Inspite of the suvering of the people in the Umayyade period from the high price of thefood- stuff because of the natural disaster monopolies, emigration from country to city, and the civil wars . inspite of what had been mentioned the Umayyad didn’t pricing . when Ummar b. Abd Alaziz had been asked to put the pricing, he refused that, because the Prophet didn’t do when he had been asked.